Lapu-lapu an adaptation - Jusay, Alexander Hernandez
"I have always envied foreign animation icons. They dominate our local television and movies. Because of the lack of local cartoons, I have always yearned to create an animation based on Philippine literature and history. Lapu-Lapu is our first national hero. As such an important historical figure, I think he deserves to be acknowledged and become famous not only in history books and in high school text, but also as part of our cultural icon. This Lapu-Lapu adaptation is my contribution in making Lapu-Lapu an icon. He can exist as a hero in fiction and fact, or in history and literature. I want Lapu-Lapu to be an icon found in comic books, cartton, games, novelty item, film and TV series, just as what Darna and Panday has become, as famous soap-opera characters. This animation is my own version of Lapu-Lapu, whom I can identify with - an icon of local content. My story adds several characters and twist to give more momentum in building Lapu-Lapu's character from an ordinary slave to becoming a Datu of Mactan. What made him Datu is not of royal roghts but of inner strength and character. Based on my resaerch, I learned that there are several versions of Lapu-Lapu history. online encyclopedias differ in their text and there are ongoing research disproving Pigafetta's journal, from which much of history is based. Moreover, these historical accounts focus on Magellan and little has been noted about Lapu-Lapu. I do believe that Pigafetta's journals are not accurate. His journals are biased to save his life from the wrath of the king of Spain. I believe that history should be changed to reflect other research, including oral history passed from generations. Since there are so many versions of this part of history, I made several changes to the story of Lapu-Lapu. I added several interpolated characters and changed some events. These changes reflect what I believed transpired during those times. I am in essence revising history by putting historical figures like Lapu-Lapu and Magellan in a fictional setting."